Effect of Coconut oil ointment on the symptom of Hemorrhoids in pregnant women: Randomized clinical trial - Elahe Jesmani; Samira Ebrahimzadeh Zagami; Masoumeh Kordi; Hassan Rakhshandeh; Seyed Reza Mazloom; Nayereh Ghomian (Mashhad University of Medical Sciences, 2020)
Introduction: Hemorrhoids is one of the most common problems during pregnancy. Lifestyle modification recommendations are associated with patients' noncompliance. The potential therapeutic properties of coconut oil on hemorrhoids have been suggested, but its scientific evidence has not been reported, therefore this study was performed with aim to determine the effect of coconut oil ointment on hemorrhoids symptoms in pregnant women. Methods: This randomized clinical trial was performed on 60 pregnant women referred to comprehensive health services centers in Mashhad in 2018-2019. The subjects were randomly divided into intervention and control groups. In the intervention group, one applicator of coconut oil ointment was applied twice a day for two weeks; they also received lifestyle modification recommendations. The control group only received lifestyle modification recommendations based on national guidelines. The improvement of hemorrhoids symptoms was measured on the first, seventh and fourteenth days using Visual Analog Scale (pain, prolapse, itching and overall score of hemorrhoid symptom). Data were analyzed using SPSS software (version 16) and Mann-Whitney, Independent T and Friedman tests. P<0.05 was considered statistically significant. Results: The mean score of pain, prolapse, itching and overall score of hemorrhoid symptoms in coconut oil ointment group significantly decreased compared to the control group (p<0.05). In the intra-group evaluation, in the coconut oil ointment group, the pain score measured by day was significantly different (p<0.001) but in control group this difference was not significant (p=0.050). Conclusion: Coconut oil ointment is effective in improving the hemorrhoids symptoms, therefore it is recommended for pregnant women with hemorrhoids grade 1 and 2.